2010
DOI: 10.1021/np1004856
|View full text |Cite
|
Sign up to set email alerts
|

4-Formylaminooxyvinylglycine, an Herbicidal Germination-Arrest Factor from Pseudomonas Rhizosphere Bacteria

Abstract: A new oxyvinylglycine has been identified as a naturally occurring herbicide that irreversibly arrests germination of the seeds of grassy weeds, such as annual bluegrass (Poa annua), without significantly affecting the growth of established grass seedlings and mature plants or germination of the seeds of broadleaf plant species (dicots). Previously, Pseudomonas fluorescens WH6 and over twenty other rhizosphere bacteria were isolated and selected for their ability to arrest germination of P. annua seeds. The Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 26 publications
1
44
0
1
Order By: Relevance
“…In some reports, inoculation with bacteria has promoted seed germination and rate (Ashrafuzzaman et al, 2009;Selvakumar et al, 2009;Zarrin et al, 2009;Noumavo et al, 2013), while in some other reports it has been found to decrease seed germination (Banowetz et al, 2008;McPhail et al, 2010). For example, Selvakuma et al (2009) reported that P. fragi CS11RH1, an IAA-producing strain, significantly increased the germination percentage and rate, plant biomass and nutrient uptake of wheat seedlings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In some reports, inoculation with bacteria has promoted seed germination and rate (Ashrafuzzaman et al, 2009;Selvakumar et al, 2009;Zarrin et al, 2009;Noumavo et al, 2013), while in some other reports it has been found to decrease seed germination (Banowetz et al, 2008;McPhail et al, 2010). For example, Selvakuma et al (2009) reported that P. fragi CS11RH1, an IAA-producing strain, significantly increased the germination percentage and rate, plant biomass and nutrient uptake of wheat seedlings.…”
Section: Discussionmentioning
confidence: 99%
“…For example, some of the bacteria in this group are known to be pathogenic (Hirano & Upper, 2000), while others are known to be involved in disease suppression (Halgren et al, 2011). In addition, some members of this group of bacteria appear to increase seed germination (Selvakumar et al, 2009), while others exert inhibitory effects on seed germination (McPhail et al, 2010;Lee et al, 2013). Germination arrest factors (GAFs) have been the subject of increased research in recent years.…”
Section: Bacteria Strains and Growth Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…57. In earlier studies, Brimecombe et al (2007) and McPhail et al (2010) also observed an inhibition of plant growth by plant-associated bacteria. Several bacterial metabolites such as phytotoxins, cyanide and nonvolatile compound can inhibit plant growth (Banowetz et al 2008).…”
Section: Discussionmentioning
confidence: 83%
“…This compound, which we termed a Germination-Arrest Factor (GAF), selectively and irreversibly arrests the germination of a large number of graminaceous species, including a number of invasive grassy weeds [10]. We identified GAF as the non-proteinogenic amino acid 4-formylaminooxyvinylglycine (FVG, L-2-amino-4-formylaminooxy- trans- 3-butenoic acid) [12]. FVG was subsequently shown to also have selective antimicrobial activity against a few strains of bacteria (13), including Erwinia amylovora , the bacterial plant pathogen that is the causal agent of the disease of orchard crops known as fireblight.…”
Section: Introductionmentioning
confidence: 99%